Hybrid Model Based on Technology Acceptance Model (TAM) & Information System Success Model (ISSM) in Analyzing the Use of E-Health - Krisdina Shinta; Dwi Nurhayati Oky; Mutiara Kusumo Nugraheni Dinar (E3S Web of Conferences, 2022)
Electronic health or commonly known as e-health is defined as the use of information and communication technology in supporting the health and health-related fields. The outbreak of the Covid-19 virus in 2019 has led to a massive increase in the use of e-health, therefore it is important to know how users accept e-health. To analyze e-health acceptance, we combined the extended TAM model with enhanced care and increased accessibility and ISSM. A total of 121 data were collected using a structured questionnaire. The data that has been collected was analyzed using PLS-SEM. From the tests that have been carried out, it is known that the enhanced care, perceived usefulness, perceived ease of use, attitude, information quality, satisfaction have a significant influence on usage intentions, while the increased accessibility, net benefit, service quality, and system quality factors have no significant effect on intention to use.